Comparative Review of the Potential of 177Lu-PSMA-617 and Docetaxel Chemotherapy in the Treatment of Metastatic Castration-Resistant Prostate Cancer (mCRPC) - Rahmawati, N. Anna Sakinah Liana; Hutapea, Ezra Calista; Holik, Holis Abdul (Indonesian Journal of Cancer, 2025)
Background: Prostate cancer has witnessed a substantial rise in both prevalence and risk over the years. In 2022, it is expected to rank fourth in terms of annual cancer-related mortality.  The treatment of prostate cancer involves the administration of chemotherapy using conventional drugs such as docetaxel. The most recent advancement in treating metastatic castration-resistant prostate cancer (mCRPC) is 177Lu-PSMA-617, a radioligand therapy. This treatment combines radioactive and ligand elements, resulting in exceptionally effective outcomes. This review aims to compare the potential of 177Lu-PSMA and Docetaxel in terms of production, side effects, prostate-specific antigen (PSA) reduction, and associated costs.Methods:  This literature review examines the differences in the therapeutic effectiveness of 177Lu-PSMA-617 and docetaxel monotherapy or in combination in patients with mCRPC.  Relevant research on both treatment options was searched, focusing on human clinical trials and case reports published between 2010 and 2024. Article selection was conducted in databases such as PubMed, Scopus, Springer, Elsevier, and NCBI.Results: Based on the eight articles included in this review, 177Lu-PSMA-617 can be regarded as an alternative therapy for patients with mCRPC. 177Lu-PSMA-617 and docetaxel can both decrease PSA levels by ≥50%. However, it's important to note that 177Lu-PSMA-617 is more expensive than docetaxel. Furthermore, the adverse effects of 177Lu-PSMA-617 are relatively less severe compared to those of docetaxel.Conclusions: The comparative results between docetaxel and 177Lu PSMA demonstrate that both therapies exhibit similar efficacy in reducing PSA levels. The results indicate that radioligand therapy 177Lu-PSMA-617 can be used as an alternative treatment for mCRPC with the potential for cure and minimal side effects. The cost can be minimized by increasing the utilization of radioligand 177Lu-PSMA-617, as higher usage leads to decreased prices.